2017
DOI: 10.1103/physrevlett.119.032501
|View full text |Cite
|
Sign up to set email alerts
|

Can Tetraneutron be a Narrow Resonance?

Abstract: The search for a resonant four-neutron system has been revived thanks to the recent experimental hints reported in Phys. Rev. Lett. 116, 052501 (2016) [1]. The existence of such a system would deeply impact our understanding of nuclear matter and requires a critical investigation. In this work, we study the existence of a four-neutron resonance in the quasi-stationary formalism using ab initio techniques with various two-body chiral interactions. We employ the No-Core Gamow Shell Model and the Density Matrix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
112
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(124 citation statements)
references
References 27 publications
9
112
3
Order By: Relevance
“…The Hamiltonian matrix in the NCGSM is complex symmetric and bears complex eigenvalues. Coupling to the continuum is then present at basis level, and many-body correlations occur through configuration mixing [15,22,[25][26][27]. The widths of the eigenstates obtained in NCGSM take all particleemission channels into account, so that they are total decay widths.…”
Section: The Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Hamiltonian matrix in the NCGSM is complex symmetric and bears complex eigenvalues. Coupling to the continuum is then present at basis level, and many-body correlations occur through configuration mixing [15,22,[25][26][27]. The widths of the eigenstates obtained in NCGSM take all particleemission channels into account, so that they are total decay widths.…”
Section: The Methodsmentioning
confidence: 99%
“…There were numerous theoretical calculations taking into account inter-nucleon correlations and high-quality realistic nucleon-nucleon interactions in the frame of abinitio frameworks in recent years [8,9,[13][14][15][16][17][18][19]. The extrapolation of no-core shell model (NCSM) calculations utilizing the realistic two-body JISP16 interaction with a harmonic oscillator (HO) basis showed that tetraneutron is located near 0.8 MeV above threshold and that its width is about 1.4 MeV [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Techniques used in the construction of the Hamiltonian matrix are described in Sect. 3. The description of the JD eigensolver, implementation of a suitable preconditioner and use of angular momentum projection to ensure rotational invariance of the basis vectors are described in Sect.…”
mentioning
confidence: 99%